Deep insights into the viscosity of small molecular solutions for organic light-emitting diodes. Issue 8 (23rd January 2018) - Feng, Shu; Ma, Dongxin; Qiu, Yong; Duan, Lian
Abstract : The viscosities of small molecular solutions and the surface morphologies of the corresponding thin films are investigated, toward high-performance devices (length–width ratio = 2 : 1). Abstract : Film quality plays a significant role in the performance of solution-processed organic small molecular light-emitting diodes, while it largely depends on the precursor solution properties like solution viscosity. In order to gain deep insights therein, we dissolve four typical organic small molecules into aromatic and non-aromatic solvents, and then systematically investigate their viscosities. We find that the viscosities of small molecular solutions mainly depend on the solvent viscosity, while they are slightly enhanced with increasing solution concentration; this behavior is quite different from that of polymer solutions. Attractive solute–solvent interactions lead to more obvious enhancements and the effective volume of the flowing unit becomes larger in non-aromatic rather than in aromatic solutions. The temperature dependence of viscosity is also studied and explained by the Arrhenius equation. Raising the temperature decreases the solution viscosity, while the activation energy increases when the solution concentration increases. Moreover, we prepare spin-coated thin films and investigate the effect of various solvents and different solution concentrations on the surface morphology, finally achieving good-quality films cast from chlorobenzene with a root-mean-square of about 0.4 nm, much lower than those of the corresponding vacuum-deposited films. Our results offer deep insights into the viscosity of small molecular solutions toward fabricating high-performance devices.